The Moderating Effect of Agency Cost on the Relationship Between Capital Structure and Financial Performance: Evidence of an Emerging Market - Shirwan Rafiq Sdiq; Hariem A. Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
This study investigates the relationship between capital structure and financial performance. It also examines the moderating effect of agency theory on the proposed relationship. Panel secondary data is collected for 11 industry firms quoted on the Iraqi Stock Exchange during the period 2004-2020. Financial performance is measured using ROA and MBV. According to the data analysis, the study findings confirm that capital structure has a significant negative effect on ROA but positively effects MBV. Regarding the moderating effect of agency cost, there are strong interactions in the model, which indicate that AUR has a significant impact. Moreover, firm size as a control variable has a positive impact on firm performance. These results support the agency theory argument from an emerging country. The results provide significant insights for managers of the sector, particularly for the current rapid development of the sector.